Дифференциальные подходы к диагностике хронической абдоминальной ишемии - О. Ш. Ойноткинова; С. А. Белякин; Д. А. Мироненко (Архивъ внутренней медицины, 2011)
The article presents the results of examination of patients with chronic abdominal ischemia with hemodynamically significant unpaired visceral branches of the abdominal aorta lesion. Functional classes of chronic abdominal ischemia are defined. It allows to estimate clearly the disease progress in patients with intravazal and extravasal stenosis and to justify further treatment strategy.